A New Architecture of Morphing Wing Based on Hyperelastic Materials and Metastructures With Tunable Stiffness - Xiao, Liping; Zhao, Haifeng; Xu, Zhao; Li, Xiaoyu; Shen, Chengcheng; Wang, Ke; Zhang, Lu (Frontiers in Mechanical Engineering, 2022)
Morphing wings with the ability of shape changing may enlarge flight envelop of air vehicles. This is particularly important for small-scale aircrafts demanding maneuverability and adaptability in dynamic environments. However, to design shape-changing mechanism suitable for small drones is very challenging due to extreme requirements raised by dimensional constraint, actuating limits, and weight restriction in Micro Air Vehicles (MAVs). A novel design method of morphing wings is proposed for small-scale aircrafts in this paper. The morphing wing is composed of a heterogeneous architecture, including three components: a longitudinal spar with pneumatic actuators, chordwise stiffening ribs with cable-driven metastructures and a compliant skin. Through employing both pneumatic networks with hyperelastic behavior and modified pantographic metastructures with tunable stiffness, structural deformation along both spanwise and chordwise may be controlled parametrically. Mechanical behaviors of this morphing wing were investigated thoroughly by theorical analysis, numerical verification, and experimental validation. Theorical predictions agree well with the results of 3D Finite Element Method (FEM). With optimal design determined through design of experiment (DOE) and FEM, prototyped morphing wings were fabricated accordingly. The aerodynamic performance was examined by a wind tunnel test with a Particle Image Velocimetry (PIV) instrument. Results demonstrate the efficiency and capacity of this morphing wing to adjust aerodynamic layout of aircraft in low-speed airflow environment. This proposed design provides a promising solution applicable to small-scale aircrafts with morphing wings.